2020
DOI: 10.1155/2020/7436920
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ROS Scavenging and Anti‐Inflammatory Activities of Oroxylum indicum Kurz (L.) Extract in LPS plus IFN‐γ‐Activated RAW264.7 Macrophages

Abstract: Oroxylum indicum (L.) Kurz has been used as plant-based food and herbal medicine in many Asian countries. The aim of the present study was to examine the antioxidant and anti-inflammatory activities of O. indicum extract (O. indicum) in RAW264.7 cells activated by LPS plus IFN-γ. The phytochemical compounds in O. indicum were identified by GC-MS and LC-MS/MS. Five flavonoids (luteolin, apigenin, baicalein, oroxylin A, and quercetin) and 27 volatile compounds were found in O. indicum. O. indicum presented antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Hematoxylin and eosin staining showed that unstimulated RAW 264.7 cells macrophages were almost all small and round, whereas those treated with LPS were flat and spindle-shaped and showed many dendritic-like structures typical of activated macrophages [22]. The treatment with T. lutea F&M-M36 extract, as well as with FX, significantly reduced the number of cells with dendritic structures (p < 0.001 and p < 0.01, respectively), an effect similar to that exerted by Celecoxib (p < 0.001).…”
Section: Comparative Effects Of T Lutea Fandm-m36 Extract and Fx On Cell Morphologymentioning
confidence: 97%
“…Hematoxylin and eosin staining showed that unstimulated RAW 264.7 cells macrophages were almost all small and round, whereas those treated with LPS were flat and spindle-shaped and showed many dendritic-like structures typical of activated macrophages [22]. The treatment with T. lutea F&M-M36 extract, as well as with FX, significantly reduced the number of cells with dendritic structures (p < 0.001 and p < 0.01, respectively), an effect similar to that exerted by Celecoxib (p < 0.001).…”
Section: Comparative Effects Of T Lutea Fandm-m36 Extract and Fx On Cell Morphologymentioning
confidence: 97%
“…As previously described, the changes of phenotype features were observed at higher absorbance of 2960 cm À1 and 2850 cm À1 in response to Oroxylum indicum-treated activated RAW 264.7 cells. 21 The second derivative spectra mainly revealed the elevation of lipid and membrane phospholipid which might be due to the accumulation of lipid and the alteration of cell membrane in the inflammatoryinduced cells. The increase of lipid content was also observed in diclofenac pretreatment of LPS-stimulated cells.…”
Section: Tentative Identification Namementioning
confidence: 99%
“…Volatile oils including 2-Furancarboxaldehyde, 5-(hydroxymethyl), Nonanoic acid, n-Decanoic acid, 2-Cyclohexen-1-one, 2-methyl, 2-Dodecenoic acid, Benzeneethanol, 4-hydroxy, 3-Hydroxy-2-methylbenzaldehyde, Cyclobutanecarboxylic acid, decyl ester, Dodecanoic acid, Ethyl N-(o-anisyl) formimidate, 1,6-Dihydro-5-(2-hydroxyethyl)-4-methyl-6-oxopyrimidine, Tetradecanoic acid, Hexadecanoic acid, methyl ester, n-Hexadecanoic acid, Hexadecanoic acid, ethyl ester, Phytol, Linoleic acid ethyl ester, Linolenic acid ethyl ester, Glycerol 1,3-dipalmitate, Linolelaidic acid, methyl ester, 9,12,15-Octadecatrienoic acid, 2-phenyl-1,3-dioxan-5-yl ester, Dotriacontane, Glycerol 1-monopalmitate, β-Monolinolein, Campesterol, Stigmasterol, and γ-Sitosterol are reported from the young pods (Dunkhunthod et al 2020).…”
Section: Phytochemistrymentioning
confidence: 99%
“…O. indicum exhibited significant therapeutic activities against various disorders including genotoxic (Tepsuwan et al 1992), anti-inflammatory activity (Ali et al 1998;Tenpe et al 2009;Upaganlawar et al 2009;Siriwatanametanon et al 2010;Doshi et al 2012;Tran et al 2015;Lalrinzuali et al 2016;Begum et al 2019;Dunkhunthod et al 2020), antioxidants (Ng et al 2000;Jiwajinda et al 2002;Palasuwan et al 2005;Zaveri et al 2006;Gupta et al 2008;Kalaivani and Mathew 2009;Mishra et al 2010;Joshi et al 2011;Kumar et al 2011;Singh and Kakkar 2013;Sithisarn et al 2016;Rojsanga et al 2017;Trang et al 2018), anticarcinogenic activity (Nakahara et al 2001(Nakahara et al , 2002Palasuwan et al 2005), antiarthritic activity (Laupattarakasem et al 2003;Karnati et al 2013), anticancer (breast, bladder) (Lambertini et al 2004;Lalou et al 2007;Roy et al 2007;Naveen Kumar et al 2012;He et al 2016;Nagasaka et al 2018;Yang et al 2018;Buranrat et al 2020), antitumor (Costa-Lotufo et al 2005Siriwatanametanon et al 2010), antiprotease activity (Majumdar et al 2010), gastroprotective potential or antiulcer…”
Section: Bioactivitymentioning
confidence: 99%